2018
DOI: 10.14488/bjopm.2018.v15.n2.a13
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of Lean Construction measuring tools

Abstract: The Lean Construction philosophy emerged to assist overcome the challenges in optimizing the productive processes of companies. As an effort to quantify the application degree of Lean philosophy in the civil construction companies, several measurement tools were created. In order to discuss the effectiveness of these tools into measuring the presence of the Lean philosophy in construction sites, the present study performed a critical analysis of its methodological procedures, based on four aspects: ‘questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Recently Lucena and De Mori (2018) quotes and confirm other authors that stated no extensive application of LC in the Brazilian industry nowadays. This research analyzes six MM through ten parameters distributed in four topics.…”
Section: Literature Surveysupporting
confidence: 80%
See 1 more Smart Citation
“…Recently Lucena and De Mori (2018) quotes and confirm other authors that stated no extensive application of LC in the Brazilian industry nowadays. This research analyzes six MM through ten parameters distributed in four topics.…”
Section: Literature Surveysupporting
confidence: 80%
“…Carvalho's (2008) method had a great performance about the utility of the results for processes optimization. Pereira's (2012) method was considered the most efficient MM to measure LC use (Lucena and De Mori, 2018).…”
Section: Literature Surveymentioning
confidence: 99%
“…The applied MM have distant origins, this shows how different countries are concerned about assessing performance in LC philosophy and country progress in this journey. Lucena and De Mori (2018) analysed six Brazilian MM and concluded that DOLC method was an ideal application to evaluate Brazilian companies, not just each project. Carvalho and Scheer (2017) compiled papers that applied DOLC method in Brazilian projects and observed low adhesion and knowledge of the companies to LC.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the spread of the lean production concepts, a gap can be observed between the concepts and an effective method of implementation in construction companies (Alves et al 2012;Tillmann 2014;Tommelein 2015), as well the literature presents only Lean Construction principles diagnostics through the companies (Nesensohn et al 2014;Bygballe and Sward 2014;Christoph 2014;Erol et al 2017;Lucena and De Mori 2018). Such as the application of lean tools, such as 5S, Six Sigma, Kaizen, Kanban, and others, in construction environment (Kemmer et al 2006;Marzouk et al 2011;Shang and Sui Pheng 2013).…”
Section: Introductionmentioning
confidence: 99%